The Students’ Attitude on Bilingual Based Instruction in Teaching English in Indonesian EFL Classroom - Saud, Chaerul Fadlan; Saud, Syukur; Karim, Abdul (Universitas Negeri Makassar, 2024)
Abstract. This research investigates Indonesian students' attitudes in EFL classrooms where bilingual focused curriculum is used to teach English to Indonesian EFL students. This study utilized subjective methodology as a fundamental structure of study with a contextual analysis technique. The subject of this investigation were fifty students of Indonesian EFL classroom. The data from poll were examined upheld Likert scale to explore understudies' demeanor and semi-organized meeting to find out the advantages of instructor's bilingual based guidance in educating English. This research demonstrates that understudies have a positive attitude about the instructor's bilingual language work as a language instruction in their English classroom; for workforce students studying English, there are six benefits to the instructor's bilingual language use, including finding it easy to understand what the educator explains in English exercise, feeling comfortable through the classification, and being simple to get a grip on what the educator clarify in English exercise. The results could, in theory, contribute significantly to the development of lone classroom language guidance, which may be used by a teacher in an English learning study hall, especially for showing understudies with a low level of English competence and where English is spoken as a foreign language (EFL). Keywords: Bilingual, Attitude, Teaching English, EFL classroom